Cross-sectional and longitudinal associations between total and regional white matter hyperintensity volume and cognitive and motor function in Parkinson's disease - Vincent Pozorski; Jennifer M. Oh; Ozioma Okonkwo; Stephanie Krislov; Amy Barzgari; Frances Theisen; Jitka Sojkova; Barbara B. Bendlin; Sterling C. Johnson; Catherine L. Gallagher (NeuroImage: Clinical, 2019)
Background: White matter hyperintensities (WMH) are frequently observed on T2-weighted brain magnetic resonance imaging studies of healthy older adults and have been linked with impairments in balance, gait, and cognition. Nonetheless, few studies have investigated the longitudinal effects of comorbid WMH on cognition and motor function in Parkinson's disease. Methods: The Lesion Segmentation Tool for Statistical Parametric Mapping was used to obtain total lesion volume and map regional WMH probabilities in 29 PD and 42 control participants at two study visits 18 months apart. Both cross-sectional and longitudinal comparisons were made between composite scores in the domains of executive function, memory, and language, and Unified Parkinson's Disease Rating Scale (UPDRS) scores. Results: We found no difference between disease and control groups in total WMH volume or progression during the study. Greater regional and global WMH at baseline was more strongly associated with lower executive function in PD subjects than in controls. Increased regional WMH was also more strongly associated with impaired memory performance in PD relative to controls. Longitudinally, no associations between cognitive change and total or regional WMH progression were detected in either group. A positive relationship between baseline regional WMH and total UPDRS scores was present in the control group, but not PD. However, greater WMH increase was associated with a greater increase in UPDRS motor sub-scores in PD. Conclusions: These findings suggest that although PD patients do not experience greater mean WMH load than normal aged adults, comorbid WMH do exacerbate cognitive and motor symptoms in PD. Keywords: Aged, Cognitive impairment, Magnetic resonance imaging, Neuroimaging, Parkinson's disease/pathology*, White matter hyperintensities